The prevalence of herbal medicine among Sudanese adults: a cross-sectional study 2021 - Raheeg Mohamed; Reham Mohamed; Rana Dafalla; Aya Ahmed; Abdulrahman Abdeldaim (BMC, 2024)
Abstract Background The use of herbal medicine has a long history in Sudan and is widely practiced among the general population. However, there is a lack of studies examining the prevalence, patterns, and predictors of herbal medicine usage in Sudan. Thus, this study was conducted to bridge this gap. Methods This descriptive cross-sectional study was conducted between January and February 2021. It included Sudanese adults residing in Omdurman, Sudan, using systematic and simple random sampling methods. Data were collected using a structured, adapted questionnaire comprising: the socio-demographic characteristics and the knowledge of herbal medicine and its usage. Moreover, it investigated the commonly used herbal remedies and the participants' sources of information and procurement of such products. Additionally, we examined the correlation between socio-demographic factors, cultural beliefs, and the use of herbal medicine. Data were analyzed using SPSS, and categorical data were presented as frequencies and percentages. Associations were assessed using chi-square, Fisher's exact tests, and binary logistic regression (p < 0.05). Results This study included 381 participants, of which 48.1% were females and 31.4% were aged 20-30. The majority of participants were aware of the practice of herbal medicine and the prevalence of its usage was 85.9%. Peppermint, acacia, hibiscus, ginger, and fenugreek were the most commonly used remedies. Chi-square and Fisher's exact testing revealed that the participants' gender and beliefs in the safety and effectiveness of herbal medicines were significantly associated with herbal medicine usage (p < 0.05). Binary logistic regression analysis showed that only the perception of herbal medicine's safety was an independent predictor of its usage (p-value 0.038). Conclusion This study reported a very high prevalence of herbal medicine usage, highlighting the acceptability of Sudanese adults towards herbal medicine usage. This prompts further studies to explore their safety, efficacy, and the possibility of their integration into mainstream healthcare practices and policies.